2008
DOI: 10.1186/1532-429x-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and myocardial perfusion immediately following maximal treadmill exercise inside the MRI room

Abstract: Treadmill exercise stress testing is an essential tool in the prevention, detection, and treatment of a broad spectrum of cardiovascular disease. After maximal exercise, cardiac images at peak stress are typically acquired using nuclear scintigraphy or echocardiography, both of which have inherent limitations. Although CMR offers superior image quality, the lack of MRI-compatible exercise and monitoring equipment has prevented the realization of treadmill exercise CMR.It is critical to commence imaging as quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Using a treadmill near the MRI, Jekic et al demonstrated a threefold increase in CO with exercise in healthy volunteers [16]. The main drawback of this treadmill system is the repositioning time between the exercise and imaging, which allows significant heart rate recovery in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a treadmill near the MRI, Jekic et al demonstrated a threefold increase in CO with exercise in healthy volunteers [16]. The main drawback of this treadmill system is the repositioning time between the exercise and imaging, which allows significant heart rate recovery in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The response of cardiac hemodynamics to exercise stress has been previously studied with MRI [16,[24][25][26]. Using a treadmill near the MRI, Jekic et al demonstrated a threefold increase in CO with exercise in healthy volunteers [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective methods to produce a diagnostic quality ECG would be of great clinical benefit. There are three main applications during which this knowledge is useful: 1) MRI guided surgery (McVeigh et al 2006; Saikus and Lederman 2009; Lederman 2005; George et al 2011), 2) intracardiac electrophysiology (Susil et al 2002) and 3) stress testing by MRI (Cheng et al 2005; Jekic et al 2008, 2010). However, in order to develop a tool which can provide a useful ECG during MRI, realistic models of the MHD effect are required.…”
Section: Introductionmentioning
confidence: 99%
“…9 Our group recently developed a completely MR-compatible treadmill system that can be placed immediately next to the MR scanner table, minimizing the time to stress CMR image acquisition. 10,11 Although single-center data suggest feasibility of in-room exercise CMR, 12,13 prospective evaluation in a multicenter trial including both community and academic practices has been lacking. In this work we evaluated the diagnostic performance of exercise stress testing by CMR compared to SPECT as the reference standard with additional comparison to coronary angiography.…”
mentioning
confidence: 99%